2020
DOI: 10.1055/s-0039-1701008
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Leakage after Surgery for Neuroblastoma: A Rare Complication?

Abstract: Introduction Neuroblastoma is the most common extracranial solid tumor in infancy. It is responsible for around 15% of all oncological deaths during childhood. Due to its retroperitoneal location, neuroblastoma is invasively growing directly in and around the lymphatic duct. Consecutively, lymphatic leakage (LL) after surgery for neuroblastoma is a known complication. The purpose of this study is the investigation of frequency and impact of this complication. Material and Methods Between February 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In recent years, there are many differences in the choice of treatment in some studies of lymphatic leakage after NB surgery. Froeba-Pohl [ 8 ] found that there was a trend toward shorter duration of lymphatic leakage if either no special therapy was chosen or TPN was administered. Qureshi [ 9 ] used fat-free/low-fat diet of MCT and Pio [ 11 ] used TPN with octreotide to treat lymphatic leakage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, there are many differences in the choice of treatment in some studies of lymphatic leakage after NB surgery. Froeba-Pohl [ 8 ] found that there was a trend toward shorter duration of lymphatic leakage if either no special therapy was chosen or TPN was administered. Qureshi [ 9 ] used fat-free/low-fat diet of MCT and Pio [ 11 ] used TPN with octreotide to treat lymphatic leakage.…”
Section: Discussionmentioning
confidence: 99%
“…S1 ). Although two studies on lymphatic leakage after NB surgery define major abdominal drainage (greater than 300 ml/day and 400 ml/day) as lymphatic leakage [ 8 , 10 ], there may be significant differences in the amount of drainage among children with different body weight. Therefore, this diagnostic criterion may not be suitable for all children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations